You are on page 1of 20

Contents:

A

B

# 13

x

2 =

k

The Null Factor law

• C Completing the square

• D Problem solving (Quadratic equations) The quadratic formula (Extension) More difficult equations (Extension)

E

F

318

(Chapter 13)

Equations of the form

ax + b = 0

are called linear equations and have only one solution.

For example,

3x ¡ 2=0 solution, x =

is a linear equation (a = 3 and b = ¡2) and has the one

2

• 3 .

Quadratic equations can be written in the form

ax 2 + bx + c = 0.

Quadratic equations may have two, one or zero solutions. We can demonstrate this with some examples.

 Equation ax 2 + bx + c = 0 form a b c Solutions x 2 ¡ 4=0 x 2 + 0x ¡ 4=0 1 0 ¡4 x = 2 or x = ¡2 two (x ¡ 2) 2 = 0 x 2 ¡ 4x +4=0 1 ¡4 4 one x = 2 x 2 +4=0 x 2 + 0x +4=0 1 0 none as x 2 is always > 0 4 zero

Now consider the example, x 2 + 3x ¡ 10 = 0

 if x = 2, x 2 + 3x ¡ 10 and if x = ¡5, x 2 + 3x ¡ 10 = 2 2 + 3 £ 2 ¡ 10 = (¡5) 2 + 3 £ ¡5 ¡ 10 =4+6 ¡ 10 = 0 25 ¡ 15 ¡ 10 = 0 = Because x = 2 and x = ¡5 both satisfy the equation x 2 +3x ¡ 10 = 0 we say that they

are solutions of it. But, how do we find these solutions without using trial and error?

 OPENING PROBLEM

Acme Leather Jacket Co. makes and sells

• x leather jackets each day and

their revenue function is given by

R = 12:5x 2 ¡ 550x + 8125 dollars.

How many jackets must be made and sold each week in order to obtain income of \$3000 each week?

Clearly we need to solve the equation:

i.e.,

12:5x 2 ¡ 550x + 8125 = 3000 12:5x 2 ¡ 550x + 5125 = 0

How can we solve this equation?

(Chapter 13)

319

A
OF THE FORM x
2 =
k
 Consider the equation x 2 ¡ 7=0 i.e., x 2 = 7 (adding 7 to both sides) Notice that p 7 £ p 7=7, so x = p 7 is one solution and (¡ p 7) £ (¡ p 7) = 7, so x = ¡ p 7 is also a solution. Thus, if x 2 = 7, then x = § p 7: § ~`7 is read as ‘plus or minus the square root of 7 ’ SOLUTION OF x 2 = k (REVIEW) 8 > x = § p k if k > 0 If x 2 = k then < x = 0 if k = 0 > : there are no real solutions if k < 0 Example 1 Solve for x: a 2x 2 + 1 = 15 b 2 ¡ 3x 2 = 8 a 2x 2 + 1 = 15 ) 2x 2 = 14 ftake 1 from both sidesg ) x 2 = 7 fdivide both sides by 2g ) x = § p 7 b 2 ¡ 3x 2 = 8 ) ¡3x 2 = 6 ftake 2 from both sidesg ) x 2 = ¡2 fdividing both sides by ¡3g which has no solutions as x 2 cannot be < 0: EXERCISE 13A 1 Solve for x: a x 2 = 16 b 2x 2 = 18 c 3x 2 = 27 d 12x 2 = 72 e 3x 2 = ¡12 f 4x 2 = 0 g 2x 2 + 1 = 19 h 1 ¡ 3x 2 = 10 i 2x 2 + 7 = 13

320

(Chapter 13)

 Example 2 Solve for x: a (x ¡ 3) 2 = 16 b (x + 2) 2 = 11 a (x ¡ 3) 2 = 16 b (x + 2) 2 = 11 ) x ¡ 3 = § p 16 ) x +2= § p 11 ) x ¡ 3 = §4 ) x = ¡2 § p 11 ) x = 3 § 4 ) x = 7 or ¡1 2 Solve for x: a (x ¡ 2) 2 = 9 b (x + 4) 2 = 25 c d (x ¡ 4) 2 = 2 e (x + 3) 2 = ¡7 f g (2x + 5) 2 = 0 h (3x ¡ 2) 2 = 4 i
Did you notice that for
equations of the form
2
(xa
§ )= k
we did not expand the
LHS?
(x + 3) 2
= ¡1
(x + 2) 2 =
0
1
3 (2x ¡ 1) 2 = 8
B
THE NULL FACTOR LAW
When the product of two (or more) numbers is zero, then at least one of them must be zero,
i.e.,
if
ab = 0
then
a = 0
or
b = 0.
 Example 3 Solve for x using the Null Factor law: a 3x(x ¡ 5) = 0 b (x ¡ 4)(3x + 7) = 0 a 3x(x ¡ 5) = 0 b (x ¡ 4)(3x + 7) = 0 ) 3x = 0 or x ¡ 5=0 ) x ¡ 4=0 or 3x +7=0 ) x = 0 or 5 ) x = 4 or 3x = ¡7 ) x = 4 or ¡ 7 3 EXERCISE 13B 1 Solve for the unknown using the Null Factor law: a 3x = 0 b 5y = 0 c a £ 8=0 d b £ ¡2=0 e ¡7y = 0 f ab = 0 g 2xy = 0 h abc = 0 i x 2 = 0 j a 2 = 0 k pqrs = 0 l a 2 b = 0 2 Solve for x using the Null Factor law: a x(x + 3) = 0 b 2x(x ¡ 5) = 0 c (x ¡ 1)(x ¡ 3) = 0 d 4x(2 ¡ x)=0 e ¡3x(2x + 1) = 0 f 5(x + 2)(2x ¡ 1) = 0 g x 2 = 0 h 2(x ¡ 3) 2 = 0 i ¡4(2x ¡ 1) 2 = 0

(Chapter 13)

321

To use the Null Factor law when solving equations, we must have one side of the equation

equal to zero.

 Step 1: If necessary rearrange the equation with one side being zero. Step 2: Fully factorise the other side (usually the LHS). Step 3: Use the Null Factor law. Step 4: Solve the resulting linear equations. Step 5: Check at least one of your solutions.
Example 4
Solve for x:
x 2 = 3x
x 2 = 3x
) x 2 ¡ 3x
= 0
f‘equating to zero’ i.e., RHS= 0g
) x(x ¡ 3)
= 0
ffactorising the LHSg
)
x
=
0
or
x ¡ 3=0
fNull Factor lawg
)
x = 0
or
x = 3
)
x = 0 or 3
If a
£
b
= 0
then either
a
=0
or
b
=0
.
ILLEGAL CANCELLING
Let us reconsider the equation
x 2 = 3x
from Example 4.
x 2
3x
If we cancel x from both sides we have
=
and we finish with
x = 3:
x
x
Consequently, we have ‘lost’ the solution
x = 0.

From this example we conclude that:

We must never cancel a variable that is a common factor from both sides of an

equation unless we know that the factor cannot be zero.

• 3 Solve for x:

 a x 2 ¡ 7x = 0 b d x 2 = 4x e g 4x 2 ¡ 3x = 0 h

x 2 ¡ 5x = 0

3x 2

+ 6x = 0

4x 2 = 5x

c

f

i

x 2 = 8x

2x

2

+ 5x = 0

3x 2 = 9x

322

(Chapter 13)

 Example 5 Solve for x: x 2 + 3x = 28 x 2 + 3x = 28 ) x 2 + 3x ¡ 28 = 0 fone side must be 0g ) (x + 7)(x ¡ 4) = 0 fas sum = +3 and product = ¡28 gives +7 and ¡4g ) x +7=0 or x ¡ 4=0 fNull Factor lawg x = ¡7 or 4 fsolving linear equationsg
 ) 4 Solve for x: a x 2 ¡ 1=0 b x 2 ¡ 9=0 c (x ¡ 5) 2 = 0 d (x + 2) 2 = 0 e x 2 + 3x +2=0 f x 2 ¡ 3x +2=0 g x 2 + 5x +6=0 h x 2 ¡ 5x +6=0 i x 2 + 7x +6=0 j x 2 + 9x + 14 = 0 k x 2 + 11x = ¡30 l x 2 + 2x = 15 m x 2 + 4x = 12 n x 2 = 11x ¡ 24 o x 2 = 14x ¡ 49 5 Solve for x: a x 2 + 9x + 14 = 0 b x 2 + 11x + 30 = 0 c x 2 + 2x = 15 d x 2 + x = 12 e x 2 +6=5x f x 2 +4=4x g x 2 = x + 6 h x 2 = 7x + 60 i x 2 = 3x + 70 j 10 ¡ 3x = x 2 k x 2 + 12 = 7x l 9x + 36 = x 2 Example 6 Solve for x: 5x 2 = 3x + 2 5x 2 = 3x + 2 ) 5x 2 ¡ 3x ¡ 2=0 fmaking the RHS = 0g ) 5x 2 ¡ 5x + 2x ¡ 2=0 fac = ¡10, b = ¡3 ) 5x(x ¡ 1) + 2(x ¡ 1) = 0 ) numbers are ¡5 and +2g ) (x ¡ 1)(5x + 2) = 0 ffactorisingg ) x ¡ 1=0 or 5x +2=0 fNull Factor lawg ) x = 1 2 or ¡ 5 fsolving the linear equationsg 6 Solve for x: a 2x 2 +2=5x b 3x 2 + 8x = 3 c 3x 2 + 17x + 20 = 0 d 2x 2 + 5x = 3 e 2x 2 + 5 = 11x f 2x 2 + 7x +5=0 g 3x 2 + 13x +4=0 h 5x 2 = 13x + 6 i 2x 2 + 17x = 9 j 2x 2 + 3x = 5 k 3x 2 + 2x = 8 l 2x 2 + 9x = 18

(Chapter 13)

323

 Example 7 Solve for x: 10x 2 ¡ 13x ¡ 3=0 10x 2 ¡ 13x ¡ 3=0 fac = ¡30, b = ¡13 ) 10x 2 ¡ 15x + 2x ¡ 3=0 ) numbers are ¡15 and 2g ) 5x(2x ¡ 3) + 1(2x ¡ 3) = 0 ffactorising in pairsg ) (2x ¡ 3)(5x + 1) = 0 fcommon factor factorisationg ) 2x ¡ 3=0 or 5x +1=0 fusing the Null Factor lawg 3 2 or 1 fsolving the linear equationsg ) x = ¡ 5
• 7 Solve for x:

 a 6x 2 + 13x = 5 b 6x 2 = x + 2 c 6x 2 + 5x +1=0 d 21x 2 = 62x + 3 e 10x 2 + x = 2 f 10x 2 = 7x + 3 8 Solve for x by first expanding brackets and then equating to zero: a x(x + 5) + 2(x + 6) = 0 b x(1 + x) + x = 3 c (x ¡ 1)(x + 9) = 8x d 3x(x + 2) ¡ 5(x ¡ 3) = 17 e 4x(x + 1) = ¡1 f 2x(x ¡ 6) = x ¡ 20
C
COMPLETING THE SQUARE

Try as much as we like, we will not be able to solve quadratic equations such as

x 2 + 4x ¡ 7=0 by using the factorisation methods already practised. This is because the

solutions are not rationals.

To solve this equation we need a different technique.

 Consider the solution to the equation (x + 2) 2 = 11 ) x +2= § p 11 ) x = ¡2 § p 11 However, if (x + 2) 2 = 11 then x 2 + 4x + 4 = 11 and x 2 + 4x ¡ 7=0 and so the solutions to x 2 + 4x ¡ 7=0 are the solutions to (x + 2) 2 = 11: Consequently, an approach for solving such equations could be to reverse the above argument. Consider x 2 + 4x ¡ 7=0 ) x 2 + 4x = 7 ) x 2 + 4x + 4 = 7 + 4 ) (x + 2) 2 = 11 ) x +2= § p 11

) x = ¡2 § p 11

Hence the solutions to x 2 + 4x ¡ 7=0 are x = ¡2 § p 11.

324

(Chapter 13)

From the above example it can be seen that a perfect square needs to be created on the left

hand side. The process used is called completing the square.

From our previous study of perfect squares we observe that:

 (x + 3) 2 = x 2 + 2 £ 3 £ x + 3 2 notice that 3 2 = µ 2 £ 3 2 ¶ 2 (x ¡ 5) 2 = x 2 ¡ 2 £ 5 £ x + 5 2 notice that 5 2 = µ 2 £ 5 2 ¶ 2 (x + p) 2 = x 2 + 2 £ p £ x + p 2 notice that p 2 = µ 2 £ p 2 ¶ 2

i.e.,

the constant term is “the square of half the coefficient of x”.

Example 8
To create a perfect square on the LHS, what must be added to both sides of
the equation
a
x 2 + 8x = ¡5
b
x 2 ¡ 6x = 13?
What does the equation become in each case?
a
In x 2 + 8x = ¡5,
half the coefficient of x is 8
= 4
2
so, we add 4 2 to both sides
and the equation
becomes
x 2 + 8x + 4 2 =
¡5 + 4 2
(x + 4) 2
=
¡5 + 16
Notice that we keep the
equation balanced by
(x + 4) 2
= 11
sides of the equation.
b
In x 2 ¡ 6x = 13,
half the coefficient of x
is
¡6 = ¡3
2
so, we add (¡3) 2 = 3 2 to both sides
and the equation becomes
x 2 ¡ 6x + 3 2
=
13 + 3 2
(x ¡ 3) 2
=
13 + 9
(x ¡ 3) 2 = 22

EXERCISE 13C

• 1 For each of the following equations:

• i find what must be added to both sides of the equation to create a perfect square on the LHS

• ii write each equation in the form (x + p) 2 = k

a

d

g

x

2

+ 2x

= 5

x

2

¡ 6x = ¡3

x

2

+ 12x = 13

b

e

h

x

2

¡ 2x = ¡7

x

2

+ 10x = 1

x

2

+ 5x = ¡2

c

f

i

x

2

+ 6x

= 2

x

2

¡ 8x

= 5

x 2 ¡ 7x = 4

(Chapter 13)

325

 Example 9 Solve for x by completing the square, leaving answers in surd form: a x 2 + 2x ¡ 2=0 b x 2 ¡ 4x +6=0 a x 2 + 2x ¡ 2=0 ) x 2 + 2x = 2 fmove constant term to RHSg ) x 2 + 2x + 1 2 = 2 + 1 2 fadd ( 2 2 ) 2 = 1 2 to both sidesg ) (x + 1) 2 = 3 ffactorise LHS, simplify RHSg ) x +1= § p 3 ) x = ¡1 § p 3 So, solutions are x = ¡1 + p 3 or ¡1 ¡ p 3: b x 2 ¡ 4x +6=0 ) x 2 ¡ 4x = ¡6 fremove the constant term to the RHSg ) x 2 ¡ 4x + 2 2 = ¡6 + 2 2 fadd (¡ 4 ) 2 = 2 2 to both sidesg 2 ) (x ¡ 2) 2 = ¡2 ffactorise the LHS, simplify the RHSg which is impossible as no perfect square can be negative ) no real solutions exist.
Remember that if
x
2 =
k
, where
k>
0
then
x
= § ~` k .
• 2 If possible, solve for x using completing the square, leaving answers in surd form:

a

d

g

x

2

¡ 4x +1=0

x

2

+ 2x ¡ 1=0

x

2

+ 6x +3=0

b

e

h

x

2

¡ 2x ¡ 2=0

x 2 + 2x +4=0

x 2 ¡ 6x + 11 = 0

c

f

i

x

2

¡ 4x ¡ 3=0

x 2 + 4x +1=0

x

2

+ 8x + 14

= 0

3

Using the method of completing the squaresolve for x, leaving answers in surd form.

a

d

x

2

+ 3x +2=0

x

2

+ x ¡ 1=0

b

e

x 2 = 4x + 8

x 2 + 3x ¡ 1=0

c

f

x 2 ¡ 5x +6=0

x 2 + 5x ¡ 2=0

• 4 3x 2 + 6x ¡ 1=0

a

To solve

by

completing the squareour first step must be to

divide both sides by 3, and this results in x 2 + 2x ¡

statement is true.

1

3

= 0.

Explain why this

b

Use completing the squareto solve

i

2x 2 + 4x ¡ 1=0

ii

3x 2 ¡ 12x +7=0

iii

5x 2 ¡ 10x +3=0

326

(Chapter 13)

D
PROBLEM SOLVING

Contained in this section are problems which when converted to algebraic form result in a

It is essential that you are successful at solving these equations using

completing the square.

factorisation

or

PROBLEM SOLVING METHOD

 Step 1: Carefully read the question until you understand the problem. A rough sketch may be useful. Step 2: Decide on the unknown quantity, calling it x, say. Step 3: Find an equation which connects x and the information you are given. Step 4: Solve the equation using one of the methods you have learnt. Step 5: Check that any solutions satisfy the equation and are realistic to the problem. Step 6: Write your answer to the question in sentence form.
 Example 10 The sum of a number and its square is 42. Find the number. Let the number be x. Therefore its square is x 2 . x + x 2 = 42 ) x 2 + x ¡ 42 = 0 frearrangingg ) (x + 7)(x ¡ 6) = 0 ffactorisingg ) x = ¡7 or x = 6 Check: If x = ¡7, ¡7+(¡7) 2 = ¡7 + 49 = 42 X If x = 6, 6+6 2 = 6 + 36 = 42 X So, the number is ¡7 or 6.

EXERCISE 13D

• 1 The sum of a number and its square is 90. Find the number.

• 2 The product of a number and the number decreased by 3 is 108. Find the two possible answers for the number.

• 3 When 32 is subtracted from the square of a number the result is six times the original number. Find the number.

• 4 The sum of two numbers is 9 and the sum of their squares is 153. Find the numbers.

• 5 Two numbers differ

by

5 and the sum of their

squares

is 17. Find the numbers.

(Chapter 13)

327

 Example 11 A rectangle has length 5 cm greater than its width. If it has an area of 84 cm 2 , find the dimensions of the rectangle. If x cm is the width, then (x + 5) cm is the length. Now area = 84 cm 2 (x 5) cm ) x(x + 5) = 84 ) x 2 + 5x = 84 x cm ) x 2 + 5x ¡ 84 = 0 ) (x + 12)(x ¡ 7) = 0 fon factorisationg ) x = ¡12 or 7: But x > 0 as lengths are positive quantities, ) x = 7 ) the rectangle is 7 cm by 12 cm.
 6 A rectangle has length 5 cm greater than its width. Find its width given that its area is 150 cm 2 . 7 A triangle has base 2 cm more than its altitude. If its area is 49:5 cm 2 , find its altitude. 8 A rectangular enclosure is made from 50 m of fencing. The area enclosed is 144 m 2 . Find the dimensions of the enclosure. 9 A rectangular pig pen is built against an existing brick fence. 24 m of fencing was used to enclose 70 m 2 . Find the dimensions of the pen.

10

11

Use the theorem of Pythagoras to find x given:

a
b
(x 8) cm
x cm
(x 7) cm
(x 2) cm
(2x 2) cm

x cm

A right angled triangle has sides 1 cm and 18 cm respectively less than its hypotenuse.

Find the length of each side of the triangle.

12

A forestry worker plants 600 pine trees. The number of pine trees in each row is 10

more than twice the number of rows. If equal numbers of pine trees were planted in

each row, how many rows did the forestry worker plant?

13

D
Y
C

ABCD is a rectangle in which AB = 21 cm.

The square AXYD is removed and the remaining

rectangle has area 80 cm 2 .

Find the length of BC.

328

(Chapter 13)

14

A, B, C and D are posts on the banks of a

20 m wide canal. A and B are 1 m apart.

If OA is the same length as CD, find how

far C and D are apart.

C
D
20 m
B
A
O

15

E
A
B
3 cm
• D AB is 2 cm longer than BE. DC is 3 cm less than twice BE.

 a Explain why triangles ABE and ACD are similar. b If BE = x cm, show that x 2 ¡ 4x ¡ 6=0: C BE =2+ p 10 cm. c Hence, show that
 Example 12 1 The sum of a number and four times its reciprocal is 8 2 : Find the number. Let the number be x. Therefore, its reciprocal is 1 : x x + 4 £ 1 x 1 = 8 2 fas the sum is 8 1 2 g x 4 17 ) 1 + x = 2 which has an LCD of 2x x 2x 4 2 17 £ x x ) £ + £ = fto achieve a common denominatorg 1 2x x 2 2 ) 2x 2 + 8 = 17x fequating the numeratorsg ) 2x 2 ¡ 17x +8=0 fequating to zerog 2x 2 ¡ x ¡ 16x +8=0 fsplitting the middle termg x(2x ¡ 1) ¡ 8(2x ¡ 1) = 0 ffactorising in pairsg ) (2x ¡ 1)(x ¡ 8) = 0 fcommon factorg 2x ¡ 1=0 or x ¡ 8=0 fNull Factor lawg So, the number is 1 x = 2 or 8 1 2 or 8. Check: 2 1 + 4 £ 2=8 2 1 1 X 8+4 £ 8 = 8 1 2 X

16

1

The sum of a number and its reciprocal is 2 12 : Find the number.

17

2

The sum of a number and twice its reciprocal is 3 3 . Find the number.

(Chapter 13)

329

• 18 A rectangular sheet of tin plate is 20 cm by 16 cm and is to be made into an open box with a base having an area of 140 cm 2 , by cutting out equal squares from the four cor- ners and then bending the edges upwards. Find the size of the squares cut out.

• 19 A rectangular swimming pool is 12 m long by 6 m wide. It is surrounded by a pavement of uniform width, the area of the pavement being

• 8 7 of the area of the pool.

a

If the pavement is x m wide, show that the area of the pavement is 4x 2 +36x m 2 .

b

Hence, show that

4x 2 + 36x ¡ 63 = 0.

• c How wide is the pavement?

• 20 A circular magnet has an inner radius x cm, an outer radius 2 cm larger and its depth is the same as the inner radius (as shown). If the total volume of the magnet is 120¼ cm 3 , find x.

2 cm
x cm
x cm
 HISTORICAL NOTE BABYLONIAN ALGEBRA

The mathematics used by the

Babylonians

was recorded on clay tablets in cuneiform.

One such tablet which has been preserved is

called

Plimpton 322

(around

1600

BC).

The Ancient Babylonians were able to solve difficult

equations using the rules we use today, such as transposing

terms and multiplying both sides by like quantities to

remove fractions. They were familiar with factorisation.

They could, for example, add 4xy to (x ¡ y ) 2 to obtain (x + y ) 2 . This was all achieved

without the use of letters for unknown quantities. However, they often used words for the

unknown.

Consider the following example from about 4000 years ago.

Problem:

Solution:

I have subtracted the side of my square from the area and the result is 870.

What is the side of the square?”

Take half of 1, which is

• 2 1 , and multiply

• 2 1 by

• 2 1 which is

1

add this to 870 to get 870 4 .

This is the square of 29

1

• 2 .

1

• 4 ;

1

2

1

to 29 2 and the result is 30, the side of the square.

Using our modern symbols: the equation is x 2 ¡ x = 870 and the solution is

x = q ( 2 ) 2 + 870 + 2 = 30.

1

1

This solution is one of the two solutions we would obtain using the Quadratic Formula.

We meet this formula in the next section.

330

(Chapter 13)

INVESTIGATION
What to do:
1
Use factorisation techniques or ‘completing the square’ where necessary
to solve:
a
x 2 + 3x = 10
b
2x 2 = 7x + 4
c
x 2 = 4x + 3
d
4x 2 ¡ 12x +9=0
e
x 2 + 6x + 11 = 0
f
4x 2 +1=8x
¡b § p b 2 ¡ 4ac
2
A formula for solving ax 2 + bx + c = 0 is x =
:
2a
Check that this formula gives the correct answer for each question in 1.
3
What is the significance of b 2 ¡ 4ac in determining the solutions of the quadratic
equation ax 2 + bx + c = 0? You should be able to answer this question from obser-
vations in 1 and 2.
4
Establish the quadratic formula by ‘completing the square’ on
ax 2 + bx + c = 0:
(Hint:
Do not forget to divide each term by a to start with.)
E

Many quadratic equations cannot be solved by factorising, and completing the square is rather

tedious. Consequently, the quadratic formula has been developed. This formula is:

.

If ax 2 + bx + c = 0,

then

¡b § p b 2 ¡ 4ac

x =

2a

Consider the Opening problem involving the Acme Leather Jacket Co. The equation we

need to solve is:

12:5x 2 ¡ 550x + 5125 = 0

where

a = 12:5,

b = ¡550,

c = 5125

Using the formula we obtain x =

550 § p 46 250

25

which simplifies to x + 30:60

or

13:40 .

But as x needs to be a whole number,

each week.

x = 13 or 31 would produce income of around \$3000

The following proof of the quadratic formula is worth careful examination.

 Proof: If ax 2 + bx + c = 0, b c then x 2 + a x + a = 0 ) x 2 + b x = ¡ a ) x 2 + a x + µ b 2a ¶ 2 b = ¡

fdividing each term by a, as a 6= 0g

c

a

a + µ 2a 2

c

b

fcompleting the square on LHSg

(Chapter 13)

331

 µ x + 2a ¶ 2 b µ x + 2a ¶ 2 b = ¡ b 2 a µ 4a 4a ¶ + 4a 2 c b 2 ¡ 4ac = 4a 2 ) x + 2a b = § r b 2 ¡ 4ac 4a 2 ) x = ¡ 4a 2 i.e., ¡b § p b 2 ¡ 4ac x = 2a x 2 ¡ 2x ¡ 2=0

2a b § r b 2 ¡ 4ac

)

)

Example 13
Solve for x:
a
b
2x 2 + 3x ¡ 4=0
a
x 2 ¡ 2x ¡ 2=0 has a = 1, b = ¡2, c = ¡2
¡(¡2) § p (¡2) 2 ¡ 4(1)(¡2)
)
x =
2(1)
2
§ p 4+8
)
x =
2
2
§ p 12
)
x =
2
2
§ 2 p 3
)
x =
2
)
x = 1 § p 3